African Refugees - Falola, Toyin; Yacob-Haliso, Olajumoke (Book collections on Project MUSE., 2023)
"African Refugees is a comprehensive overview of the context, causes, and consequences of refugee's lives, discussing issues, policies, and solutions for African refugees around the world. It covers overarching topics such as human rights, policy frameworks, refugee protection, and durable solutions, as well as less-studied topics such as refugee youths, refugee camps, LGBTQ refugees, urban refugees, and refugee women. It also takes on rare but emergent topics such as citizenship and the creativity of African refugees. Toyin Falola and Olajumoke Yacob-Haliso showcase the voices and experiences of individual refugees through the sweep of history to tell the African refugee story from the long ago past through current developments, covering the full range of experience from the causes of flight to living in exile, all while maintaining a persistent focus on the complicated search for solutions. African Refugees recognizes African agency and contributions in pursuit of solutions for African refugees over time but avoids the pitfalls of the colonial gaze-where refugees are perpetually pathologized and Africa is always the sole cause of its own problems-seeking to complicate these narratives by recognizing African refugee issues within exploitative global, colonial, and neo-colonial systems of power"--